Contemporary high performance computing : from petascale toward exascale - Vetter, Jeffrey S. (Chapman & Hall/CRC computational science series, 2013)
Focusing on recent, major ecosystems in HPC, this book brings together the vast interconnected aspects behind state-of-the-art HPC. It explains all the factors involved in making the world's leading HPC centers successful, from architectures, applications, facilities, and software to scientists, administrators, and sponsors. The first part of the book examines significant trends in applications, performance, software, and hardware. The second part provides a detailed look at the ecosystem, science, and organization of particular HPC sites. The last part of the book addresses the roles of clouds and grids in HPC.